PREDICTION EXTREME PHASE OF MONSOON BREAK PERIOD IN INDONESIA - ADRIANITA (NIM : 22411315); Pembimbing : Dr. Nurjanna Joko Trilaksono, FERA
Asian monsoon has different impacts in each region of Indonesia. Monsoon break period which a long or often can cause drought. As well as active phase or an active phase follow by break then back to active again with a surge of high rainfall are also very dangerous in causing floods. Therefore, an understanding of the causes of extreme monsoon break phase are very important and accurate predictions are expected to minimize the impact and consequences. Research that has been done in the Indonesian area is only about assessing the characteristics of monsoon break, so it is not known how the predictability of monsoon breaks in Indonesia. To assess the predictability of the monsoon breaks in Indonesia this domain area of this study was divided into five clusters, namely Cluster 1 Sumatra region, Cluster 2 in Java , Bali , NTB and NTT region, Cluster 3 region of southern Borneo , Cluster 4 region of North Sulawesi , and Cluster 5 region of South Sulawesi. The methods that have been used are the correlation lag index rainfall from TRMM data, and multiple regression with three predictors OLR, surface pressure, U850, and also a third method is EOF using these predictors. Total of break days period for each cluster vary as influenced by rainfall pattern held on each cluster. For regions Cluster 1, 2 and 4 experienced a reduction of significant in total rainfall during the break. It is contrast to Cluster 3 and 5 which are only small fraction experienced a reduction in its territory. Monsoon break is also characterized by a weakening in the meridional winds from the north and weaker westerly zonal winds. The cause of the monsoon break in some areas cluster is the cyclonic vortex in west Kalimantan. Prediction of the break by using the method of correlation lag is getting the biggest hit 34 % for Cluster 1, while using EOF method, the biggest hit is 40 % for area Cluster 4.